Love Affair at Workplace: How Motif and Type Linked to Employee Work Behaviour in Male Employee Experience - Sukmahaningtyas, Rizky Asri; Syaebani, M. Irfan (Quantitative Economics and Management Studies, 2024)
Men tends to act more positively than female when it comes to romance in the workplace (Pierce et al., 1996; Powell, 1986). This research presents an exploratory assessment of workplace affairs using a qualitative approach to identify how motives and types of workplace affairs, linked on how it affect employee work behavior from a male employee experience. Social exchange theory and power dynamics approached are used to explain this phenomenon. Respondents were collected using purposive and snowball sampling methods due to the sensitive nature of the respondent criteria. The semi-structured, one-on-one in-depth interview was done to nine male employees who had and/or are engaging in workplace affair. Finding reveals motives and types of workplace affair linked to each other especially ego/fling motive with hierarchical type of relationship. Workplace affair does affect work behavior in vary ways. Additionally, male employee experienced negative effect despite them being superior or subordinate. A negative effect mentioned such as favoritism, power abused even workplace bullying. This study emphasizes more of workplace affair as the dark side of workplace romance thus enriched the findings of previous study regarding workplace affair in Indonesia especially from male employee experience.